CHEMICAL COMPOSITION OF STONES IN PAEDIATRIC UROLITHIASIS - Imran, Kiran; Zafar, Mirza Naqi; Fatima, Naureen; Ozair, Uzma; Sultan, Sajid; Rizvi, Syed Adibul Hasan (Journal of Ayub Medical College Abbottabad, 2017)
Background: Chemical composition of stones is one of the important diagnostic criteria for aetiology of stone formation and treatment to prevent recurrence. This paper reports composition of stones in children at a tertiary hospital by Fourier Transformation Infrared Spectroscopy (FTIR). Methods: Between January-June 2015, 412 urinary stones from children were analysed by FTIR. Chi-square tests were used for the comparison of categorical measurements between groups. All reported values were 2-sided and statistical significance was considered at p-value ‰¤0.05. Results: Of the 412 stones, 263 (63.8%) were renal, 101(24.5%) bladder and 48 (11.7%) ureteric. The mean age of children was 7.15±4.13 years with a M:F ratio 2.4:1. Of the 412 stones, 144(34.9%) were pure stones composed of one compound and 268(65.1%) were mixtures. Frequency of compound in stones was Ammonium Acid Urate (AAU) (65%), Calcium Oxalate (CaOx) (76.9%), Uric Acid (5%), Calcium Phosphate Apatite (7%), Whitlockite (8.4%), Struvite (4%), Cystine (0.72%) and Xanthine (2.11%). Frequency of compounds analysed in three ages groups 0-5, 6-10 and 11-15 years showed high frequency of AAU (73%) in 0-5 years as compared to (60%) in 11-15 years (p<0.018). CaOx (90%) in 11-15 as compared to (62.5%) in 0-5 years (p<0.001). Bladder stones were more prevalent in children 0-5 years (32%) vs 19% in 11-15 years (p<0.004) while renal were 75% in 11-15 years and 54% in 0-5 years (p<0.04). Conclusion: AAU stones known to be associated with malnutrition and chronic diarrhoea are highly prevalent in paediatric stones formers in our population in the kidney, bladder and ureter. Keywords: Paediatric; urolithiasis; chemical composition